Mapping Optimum Nitrogen Crop Uptake. (1st June 2017) - Villodre, J.; Campos, I.; Lopez-Corcoles, H.; Gonzalez-Piqueras, J.; González, L.; Bodas, V.; Sanchez-Prieto, S.; Osann, A.; Calera, A.
Abstract : This work proposes a methodology that uses remote sensing (RS) images to obtain optimum nitrogen crop uptake (Nuptake ) maps, for the all pixels in the image included in the field during the entire growing season. The Nuptake was determined from relationship between critical nitrogen concentration (Nc) and biomass where biomass was estimated by a crop growth model based on the water use efficiency. The paper proposes the use of this methodology in commercial wheat farm. The results are discussed with respect to field measurements of crop biomass and N concentration on different dates and in zones with different nitrogen treatments from 8 commercial wheat farms in Albacete, Spain during 2015 and 2016.